Recruitment of Women Research Participants: The Women's Health Registry at the University of Michigan - ROGERS, JULIET L. (2007)
OBJECTIVE: The goal was to develop the Women's Health Registry, a research participant database that prospectively collects detailed information on potential research subjects to assist in linking them with open research protocols and to assess investigator use and satisfaction with this Registry. METHODS: The Women's Health Registry was launched in 1999. Women aged ≥18 years were recruited to enroll in a database of women with interest in research participation and to complete a health questionnaire. Women's health researchers with IRB-approved projects were encouraged to apply for access to the Registry participants. In 2003, the first 15 investigators to use the Women's Health Registry were asked to participate in a standardized open-ended interview to assess investigator satisfaction with this recruitment tool. RESULTS: The Women's Health Registry is currently populated with 2436 women: 36.8% aged 18–34, 39.9% aged 35–54, 16.8% aged 55–69, and 6.4% aged ≥70 years. Of these women, 84% are Caucasian and 8.5% are African American. Structured interviews with 13 of the 15 investigators contacted revealed that 36.4% of the total subject enrollment recruited by these investigators was recruited from the Women's Health Registry. In addition, Registry participants were more likely to enroll in their research protocols than women contacted through other methods. Most of the investigators' expectations from the Women's Health Registry were met, except for access to menopausal women. CONCLUSIONS: The Women's Health Registry was successfully developed, and the goal of linking women with appropriate protocols was met with significant investigator satisfaction.